Pemetaan Tingkatan Cuaca Ekstrim Masing-Masing Kecamatan di Kota Kupang - Rahmawati, Arfita; Theo Tomi Pamungkas, Bella; Partini, Dwi (geoedusains: Jurnal Pendidikan Geografi, 2021)
Extreme weather is one of the natural disasters that occur in Kupang City, East Nusa Tenggara Province. Like other natural disasters, extreme weather also has a detrimental impact on people's lives. The purpose of this study was to determine the extent of extreme weather levels in each sub-district in Kupang City with mapping. This research is included in quantitative descriptive research, then the population and the sample used is Kupang City. The data collection method used the Landsat 8 OLI image interpretation and the data trajectory model. The data analysis technique used overlay analysis with the division of three classes of extreme weather levels, low, medium, and high. Based on the research results, it is 79.53% or with an area of 143.399 km2, Kupang is included in the extreme weather area with high criteria. The sub-district has the largest percentage range of high-level extreme weather in Kupang City is the Kota Lama sub-district. Meanwhile, the sub-district has the largest percentage of area to extreme weather with a low level is Alak sub-district.